Endophytic Actinobacteria from the Brazilian Medicinal Plant Lychnophora ericoides Mart. and the Biological Potential of Their Secondary Metabolites. Issue 6 (20th May 2016) - Conti, Raphael; Chagas, Fernanda Oliveira; Caraballo‐Rodriguez, Andrés Mauricio; Melo, Weilan Gomes da Paixão; do Nascimento, Andréa Mendes; Cavalcanti, Bruno Coêlho; de Moraes, Manoel Odorico; Pessoa, Cláudia; Costa‐Lotufo, Letícia Veras; Krogh, Renata; Andricopulo, Adriano Defini; Lopes, Norberto Peporine; et al.
Abstract : Endophytic actinobacteria from the Brazilian medicinal plant Lychnophora ericoides were isolated for the first time, and the biological potential of their secondary metabolites was evaluated. A phylogenic analysis of isolated actinobacteria was accomplished with 16S rRNA gene sequencing, and the predominance of the genus Streptomyces was observed. All strains were cultured on solid rice medium, and ethanol extracts were evaluated with antimicrobial and cytotoxic assays against cancer cell lines. As a result, 92% of the extracts showed a high or moderate activity against at least one pathogenic microbial strain or cancer cell line. Based on the biological and chemical analyses of crude extracts, three endophytic strains were selected for further investigation of their chemical profiles. Sixteen compounds were isolated, and 3‐hydroxy‐4‐methoxybenzamide (9 ) and 2, 3‐dihydro‐2, 2‐dimethyl‐4(1 H )‐quinazolinone (15 ) are reported as natural products for the first time in this study. The biological activity of the pure compounds was also assessed. Compound15 displayed potent cytotoxic activity against all four tested cancer cell lines. Nocardamine (2 ) was only moderately active against two cancer cell lines but showed strong activity against Trypanosoma cruzi . Our results show that endophytic actinobacteria from L. ericoides are a promising source of bioactive compounds. Abstract :